Performance et rareté des coopératives de travailleurs : contributions empiriques à partir du cas français (Scop) - Thibault Mirabel (Revue de la Régulation)
This thesis compares the performance of worker-owned firms (WOFs) and conventional firms. These types of firms differ by their distribution of ownership rights and their mode of governance. In WOFs, the ultimate control is held by the suppliers of labour, whereas in conventional firms the ultimate control is held by the suppliers of capital. WOFs represent an implementation of democracy in firms. Despite their attractiveness, WOFs represent a minute proportion of firms in our contemporary economies (2,400 in France). This thesis seeks to bring new insights and stylized facts to better understand the rarity of WOFs. Chapter 1 shows that the likelihood of WOF entry is the highest when the sunk cost of human capital is dominant while the sunk cost of physical capital is negligible. Chapter 2 shows that WOFs survive longer than conventional firms regardless of whether they have different or similar entry resources. Chapter 3 shows that any type of worker buyout, even from firms in difficulty, survives longer than newly created WOFs. Overall, this thesis suggests that the rarity of WOFs is more likely to result from entry barriers specific to WOFs rather than from poor performance compared to CFs.